The study of soil heat transfer characteristics for development of cost-saving air conditioning system using earth cool dehumidification method / Zairul Fazura Mohd Zaidi and Abdul Talib Din - Mohd Zaidi, Zairul Fazura; Din, Abdul Talib (2012)
This is a study of soil heat transfer characteristic at equator zone within latitudes ½ o and 7 o @ and longitudes 100 o to 1191/2 o E in Peninsular of Malaysia. Soil heat transfer parameters selected were thermal resistance, thermal conductivity and delta heat. Soil Canter Lab (Malaysia) uses the Proctor Test to find the maximum moisture content and optimum dry density for six samples of soil which were then used in experiment onto samples. The Dry Oven Method was used to find moisture content, Sand-Cone Method was used to find the dry density and Thermocouple was used to find the heat of soil at 100mm and 150mm depths every one minute in thirty minutes. Kersten's Method was used to calculate thermal conductivity of soil and Fourier's Law was used to calculate heat transfer for each sample of soil. Sandy type soil has a higher thermal conductivity, delta heat and soil heat transfer than the salty clay type of soil. Peninsular Malaysia was influenced by Tropical Rainforest climate. It is warm and humid for the whole year round. Higher mean annual rainfall at approximately 2300mm per annum gives advantages to develop an underground air conditioning system according to higher heat transfer of soil and for cost saving but more importantly, it is an environmentally clean system.